2019
DOI: 10.1016/j.ejvs.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol for the Prevention of Peri-Operative Acute Kidney Injury: A Systematic Review

Abstract: Post-operative acute kidney injury (AKI) is known to be an independent risk factor for both short and long-term mortality. The diuretic mannitol is often used in cardiovascular surgery and other surgical fields for renal protection. This systematic review substantiates that peri-operative use of mannitol for AKI prevention should not be considered an evidence based intervention in cardiac and vascular surgery, partial nephrectomy, and/or other major surgery. This is because data mostly derive from heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, it is well known that vascular endothelial dysfunction resulting in ischemia occurs in vulnerable organs in the diabetic setting [24,25]. In particular, the kidney is susceptible to damage by ECLS [26,27]. In this study, non-physiologic circulation by ECMO was considered closely associated with acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it is well known that vascular endothelial dysfunction resulting in ischemia occurs in vulnerable organs in the diabetic setting [24,25]. In particular, the kidney is susceptible to damage by ECLS [26,27]. In this study, non-physiologic circulation by ECMO was considered closely associated with acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 96%
“…Mannitol is an osmotic diuretic that is commonly used to relieve cerebral edema after cerebrovascular accidents. Despite conflicting data, mannitol is still commonly used in clinical practice to prevent AKI ( 42 ). Fisher et al showed that patients' renal function is preserved when mannitol is administered in open-heart surgery, which may be associated with reduced cell swelling and deposition of cellular debris in the renal tubules ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol, a six-carbon sugar polyol that exists naturally in many plants, especially in seaweeds, has many applications in the pharmaceutical, chemical, and food industries. Clinically, mannitol is widely used in the management of cerebral edema and other conditions with raised intracranial pressure. In diabetic foods, due to its low glycemic index and poor intestinal absorption, it is used as a sweetener and since it is nonhygroscopic and does not promote dental decay, it is commonly used in sweets…”
Section: Introductionmentioning
confidence: 99%